Upaya Imigrasi dalam Penerapan Sanksi Pidana Terhadap Pengguna Dokumen Perjalanan Palsu - Jerold, Jerold; Suhaidi, Suhaidi; Isnaini, Isnaini (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
The purpose of this study is to find out how the forms of falsification of the Travel Documents of the Republic of Indonesia, how the application of criminal sanctions for the forgeries of the Travel Documents of the Republic of Indonesia according to positive Indonesian law and how immigration actions in overcoming the fraudulent Travel Documents of the Republic of Indonesia occur. The research method used in this research is descriptive analysis, data collection techniques with literature studies and interviews, the types of data are primary data and secondary data, while the data analysis using descriptive cumulative data analysis is descriptive. From the results of research that cases of forgery of Travel Documents of the Republic of Indonesia (passports), can be classified into four forms of forgery of Travel Documents of the Republic of Indonesia (passports): original documents obtained illegally (using false or incorrect data), original documents that have been subjected to changes, documents that are completely falsified (duplication), original documents used by others (Impostor). Articles used in the crime of forgery of passports are article 119, article 126, article 127, article 129. Countermeasures to prevent the falsification of Travel Documents of the Republic of Indonesia, such as by: Issuance of Electronic Passport (e-passport), Photo and fingerprinting process finger recording the applicant's data, interview process when the applicant submits a passport application, Provision of Passport Safety Features.